2015
DOI: 10.1158/0008-5472.can-14-3569
|View full text |Cite
|
Sign up to set email alerts
|

CD73 Is Associated with Poor Prognosis in High-Grade Serous Ovarian Cancer

Abstract: The cell surface nucleotidase CD73 is an immunosuppressive enzyme involved in tumor progression and metastasis. Although preclinical studies suggest that CD73 can be targeted for cancer treatment, the clinical impact of CD73 in ovarian cancer remains unclear. In this study, we investigated the prognostic value of CD73 in high-grade serous (HGS) ovarian cancer using gene and protein expression analyses. Our results demonstrate that high levels of CD73 are significantly associated with shorter diseasefree surviv… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
151
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 213 publications
(168 citation statements)
references
References 40 publications
10
151
0
Order By: Relevance
“…CD73 expression in ovarian carcinoma or medulloblastoma some studies was associated with a good prognosis [103,104], while in others it was associated with a poor prognosis [94]. Interestingly, Turcotte et al observed CD73 expression mainly in stromal cells with an EMT gene signature, and they proposed that ectonucleotidase is involved in tumor invasion [94]. In recent studies, it was described that tumor-derived exosomes containing ectonucleotidases CD39 and CD73 are able to transfer an EMT program with a pro-metastatic message; the ADO produced by these enzymes exerts a negative modulation of the antitumor immune response facilitating the metastasis process [105] and reviewed in [106].…”
Section: Adora2amentioning
confidence: 98%
See 1 more Smart Citation
“…CD73 expression in ovarian carcinoma or medulloblastoma some studies was associated with a good prognosis [103,104], while in others it was associated with a poor prognosis [94]. Interestingly, Turcotte et al observed CD73 expression mainly in stromal cells with an EMT gene signature, and they proposed that ectonucleotidase is involved in tumor invasion [94]. In recent studies, it was described that tumor-derived exosomes containing ectonucleotidases CD39 and CD73 are able to transfer an EMT program with a pro-metastatic message; the ADO produced by these enzymes exerts a negative modulation of the antitumor immune response facilitating the metastasis process [105] and reviewed in [106].…”
Section: Adora2amentioning
confidence: 98%
“…However, CD73 has been part of a polemic argument regarding its involvement in the cancerous process. CD73 expression in ovarian carcinoma or medulloblastoma some studies was associated with a good prognosis [103,104], while in others it was associated with a poor prognosis [94]. Interestingly, Turcotte et al observed CD73 expression mainly in stromal cells with an EMT gene signature, and they proposed that ectonucleotidase is involved in tumor invasion [94].…”
Section: Adora2amentioning
confidence: 99%
“…Although the association between CD73/CD39 expression and patient prognosis is complex (39), in many cases the expression of CD73 has been shown to negatively correlate with patient survival. This includes patient cohorts in breast (20), ovarian (22), renal cell (40), rectal adenocarcinoma (41), and prostate cancer (42). Furthermore, targeting this pathway has been shown to enhance clinical responses to chemotherapy (20) and other classes of immunotherapy (33,43,44).…”
Section: Genetic Targeting Of a 2a R Protects Car T Cells From Adenosmentioning
confidence: 99%
“…CD73 is expressed on both tumor cells and host immunosuppressive cells such as Tregs and myeloid-derived suppressor cells (MDSCs). CD73 expression has been shown to negatively correlate with patient prognosis in a number of cancer types (20)(21)(22), highlighting the relevance of the CD73/adenosine immunosuppressive axis in patients. Furthermore, preclinical studies have shown that targeting of either CD73…”
Section: Introductionmentioning
confidence: 99%
“…In our recent study, we investigated the clinical impact of CD73 mRNA and protein expression in HGSC and assessed whether CD73 expression was associated with altered CD8 C T cell-mediated immunosurveillance. 10 First, using the Australian Ovarian Cancer Study dataset and a meta-analysis of 13 independent datasets regrouping more than 1,500 patients, we demonstrated that high levels of CD73 gene expression indeed correlated with poor prognosis (disease-free survival [DFS] and overall survival [OS]) in HGSC. When we investigated CD73 gene expression with regard to the different molecular subtypes of HGSC, we noted that CD73 was preferentially expressed in the C1/mesenchymal subtype, which is characterized by a reactive stromal.…”
mentioning
confidence: 99%